P480 Effectiveness of anti-inflammatory therapy in immune checkpoint inhibitor-induced diarrhoea/colitis. (16th January 2018) - Ibraheim, H; Samaan, M; Powell, N
Abstract: Background: Immune checkpoint inhibitors (ICPI), including monoclonal antibodies targeting CTLA-4 (e.g. ipilimumab) and PD-1 (e.g. nivolumab) have transformed the treatment landscape for several cancers. However, their success is hampered by the high incidence of immune-mediated toxicity. ICPI- induced diarrhoea/colitis, resembling some aspects of IBD, occurs in up to 46% of patients and is the most common cause of ICPI discontinuation and death. Presently, treatment of ICPI-induced colitis is ad hoc, but typically involves high-dose systemic steroids, with biologics (most commonly anti-TNF) used as rescue therapy. ICPI use is anticipated to increase substantially in coming years, and expert gastroenterology input, and development of evidence-based treatment algorithms is now urgently needed. Our aim was to conduct a systematic review on the effectiveness of anti-inflammatory therapy in the management of ICPI- induced diarrhoea/colitis. Methods: Relevant databases including Medline (PubMed and OVID), EMBASE, Web of Science and Cochrane were searched up to September 2017. Inclusion criteria included adult cancer patients treated with at least one dose of an ICPI, and reported outcome data following anti-inflammatory drug management of diarrhoea. Two independent reviewers (HI and MAS) assessed eligibility of studies. Results: After reviewing 1838 studies, 26 met the inclusion criteria (15 original articles, 11 abstracts), of which 17 (65%) were retrospective studies. A total of 983 patients were reported to have diarrhoea and/or colitis. Sixteen studies reported on anti-CTLA-4 therapy (ipilimumab or tremelimumab), 4 on anti-PD-1, and 6 on both (either anti-CTLA-4 or anti-PD-1) or combination therapy. Five hundred and fifty-eight (57%) patients were treated with corticosteroids, with clinical response reported in 333 (62%). However, reporting of the corticosteroid dose, type and regimen used was inconsistent. Two hundred and ninety-seven (30%) patients with steroid refractory disease received infliximab with impressive response rates (86%), although response rates were only reported for 188 patients. A single case series reported vedolizumab to be effective in the management of 6 out of 7 steroid refractory patients. Conclusions: ICPI-induced diarrhoea/colitis is a significant complication of cancer immunotherapy and engagement with specialist gastroenterology services are now urgently needed to improve outcomes. Systematic review of therapeutic experience in this setting indicates that about two-thirds of patients respond to high-dose steroids, and rescue therapy with biologics captures response in most steroid refractory cases. Given the predicted expansion in use of ICPI in cancer, better quality clinical data are needed to inform standardised treatment protocols.